A Giant Mucinous Adenocarcinoma Arising within a Villous Adenoma of the Urachus: Case Report and Review of the Literature - Steven Joniau; Evelyne Lerut; Hein Van Poppel (Case Reports in Medicine)
We present an exceptional case of a giant urachal tumor, consisting of both villous adenoma and mucinous adenocarcinoma of the urachus. The tumor was incidentally discovered during investigations for renal failure. Initial transurethral biopsies showed only a villous adenoma of the urachus. Although the biopsies showed no malignancy, a radical cystoprostatectomy and broad excision of the urachus and umbilicus were performed. At the same time, a bilateral nephroureterectomy was performed because of reflux-nephropathy and renal failure. The indication for surgery was based on the typical imaging aspects, raising the suspicion of an underlying urachal adenocarcinoma (size and location). Indeed, at final histopathology a concomitant well-differentiated adenocarcinoma of the urachus confined to the urachal mucosa was found. The patient remained free of disease for 50 months of follow-up. Only three previous cases of urachal adenocarcinoma associated with villous adenoma have been described.